Possibilities of Using Private Military Companies in Peacekeeping Operations of the United Nations Security Council - Kroplewski, Jarosław; Skelnik, Klaudia (Historia i Polityka, 2025)
The phenomenon of engaging mercenaries to participate in armed conflicts or conduct operations on the verge of war has been known since ancient times. The first documented mentions of armed clashes in which mercenaries took part date back to the 13th century BC and refer to the battle of Kadesh. Famous formations of Greek hoplites often served the Persian rulers. Their services were used by Alexander of Macedon, Hannibal and the rulers of the Roman Empire. Mercenaries developed most intensively during the Renaissance, where the city-states of Italy used mercenary formations. The Germans, the Swiss and the Scots were involved in mercenaries. In the First Polish Republic, the most well-known formation of this type was the Lisowczycy (the Lisowczyks). It was not until the creation of national armies at the end of the 18th century that mercenary formations disappeared. For example, the French Constituent Assembly passed a ban on the employment of mercenaries in the French state on February 28, 1790. The revival of mercenaries was influenced by the Cold War, especially the period of decolonization of Africa. At that time, mercenaries were employed by former colonizers who did not want to get rid of their dependent territories, often rich in various types of natural resources. Mercenaries played a vital role in shaping the political landscape of the world. Their extremely controversial activities were penalized at the end of the 20th century under international legal regulations. It is commonly believed that the role of mercenaries has now been taken over by private military companies (from now on: PMCs), which, unlike their predecessors, legally operate transnational companies. However, the purpose of their actions is the same as that of mercenaries, namely, to offer their services to the highest bidder. International law entities, transnational corporations, NGOs, and organised crime groups benefit from their support. Nevertheless, their existence has become a fact with which we must come to terms. Considering the excellent organization, professionalism and equipment of PMC employees, one should consider whether it would be justified to hire these companies to conduct peacekeeping operations supervised by the UN Security Council. Of course, these considerations apply to companies whose employees have not violated the applicable norms of international law.